Problematika Sopir Angkutan Kota di Kota Samarinda (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
The purpose of this study was to determine the socio-economic condition of the city transport driver, the problems faced by the city transport driver in the city of Samarinda and their strategy for ensuring the sustainability of their lives. The research method uses qualitative research with grounded theory approach and also using a participatory way. Informants in this study are the three drivers of public transport as a key informant, two incognito, and two as triangulation of data to complete this research information. The results of this study show that the socio-economic life of the city transport driver is still relatively poor families when measured from the level of revenue generated and compared to a standard poverty line of Samarinda, but the poor vulnerable in case of price increases on basic necessities. They assume that the problems in the face is that competition between the work of the Municipal Transport Drivers and Driver Vehicle Online. There is also the Land Transportation Organization (Organda) as a forum for the city's transport driver in the building and create a healthy competition among public transport drivers as well as improving the welfare of the city transport driver in the city of Samarinda.Another strategy to ensure survival, they persisted with his work as a driver of urban transportation.By collecting as many passengers, which means when the passenger deserted, they have to wait for passengers arriving and stopping at various places undue. As a result of such act led to bottlenecks in the various segments of Samarinda.